Tomato oleoresin inhibits DNA damage but not diethylnitrosamine-induced rat hepatocarcinogenesis - Scolastici, Clarissa [UNESP]; Lopes, Gisele A. D. [UNESP]; Barbisan, Luis Fernando [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2008)
Various studies have shown that lycopene, a non-provitamin A carotenoid, exerts antioxidant, antimutagenic and anticarcinogenic activities in different in vitro and in vivo systems. However, the results concerning its chemopreventive potential on rat hepatocarcinogenesis are ambiguous. The aim of the present study was to investigate the antigenotoxic and anticarcinogenic effects of dietary tomato oleoresin adjusted to lycopene concentration at 30, 100 or 300ppm (administered 2 weeks before and during or 8 weeks after carcinogen exposure) on liver of male Wistar rats treated with a single intraperitoneal dose of 20 or 100 mg/kg of diethylnitrosamine (DEN), respectively. The level of DNA damage in liver cells and the development of putative preneoplastic single hepatocytes, minifoci and foci of altered hepatocytes (FHA) positive for glutathione S-transferase (GST-P) were used as endpoints. Significant reduction of DNA damage was detected when the highest lycopene concentration was administered before and during the DEN exposure (20 mg/kg). However, the results also showed that lycopene consumption did not reduce cell proliferation in normal hepatocytes or the growth of initiated hepatocytes into minifoci positive for GST-P during early regenerative response after 70% partial hepatectomy, or the number and area of GST-P positive FHA induced by DEN (100 mg/ kg) at the end of week 10. Taken together, the data suggest a chemopreventive effect of tomato oleoresin against DNA damage induced by DEN but no clear effectiveness in initiating or promoting phases of rat hepatocarcinogenesis. (c) 2008 Elsevier GmbH. All rights reserved.
Keywords: chemoprevention; diethylnitrosamine; DNA damage; GST-P liver foci; hepatocarcinogenesis; tomato oleoresin; lycopene